Enhancing the Mitochondrial Uptake of Phosphonium Cations by Carboxylic Acid Incorporation - Pala, Laura; Senn, Hans M.; Caldwell, Stuart T.; Prime, Tracy A.; Warrington, Stefan; Bright, Thomas P.; Prag, Hiran A.; Wilson, Claire; Murphy, Michael P.; Hartley, Richard C. (Frontiers in Chemistry, 2020)
There is considerable interest in developing drugs and probes targeted to mitochondria in order to understand and treat the many pathologies associated with mitochondrial dysfunction. The large membrane potential, negative inside, across the mitochondrial inner membrane enables delivery of molecules conjugated to lipophilic phosphonium cations to the organelle. Due to their combination of charge and hydrophobicity, quaternary triarylphosphonium cations rapidly cross biological membranes without the requirement for a carrier. Their extent of uptake is determined by the magnitude of the mitochondrial membrane potential, as described by the Nernst equation. To further enhance this uptake here we explored whether incorporation of a carboxylic acid into a quaternary triarylphosphonium cation would enhance its mitochondrial uptake in response to both the membrane potential and the mitochondrial pH gradient (alkaline inside). Accumulation of aryl propionic acid derivatives depended on both the membrane potential and the pH gradient. However, acetic or benzoic derivatives did not accumulate, due to their lowered pKa. Surprisingly, despite not being taken up by mitochondria, the phenylacetic or phenylbenzoic derivatives were not retained within mitochondria when generated within the mitochondrial matrix by hydrolysis of their cognate esters. Computational studies, supported by crystallography, showed that these molecules passed through the hydrophobic core of mitochondrial inner membrane as a neutral dimer. This finding extends our understanding of the mechanisms of membrane permeation of lipophilic cations and suggests future strategies to enhance drug and probe delivery to mitochondria.